Review of the Development of the Concept of Ericson's Personality Psychology Theory in Physical Education Learning for Elementary School Children - Waffak, Muhammad Nasihul; Taryatman (CV. Nusantara Sporta, 2024)
Psychosocial Theory by Erik H. Erikson and Psychosexual Theory by Sigmund Freud. Freud introduced the school of psychoanalysis, which was further developed by Erikson into Psychosexual Theory and then Psychosocial Theory. In his book